A Decade of Open Access Funding in Qatar: from challenges to opportunities - Alwaleed Alkhaja (13761787) (2025)
Presentation was part of the 4th Annual Forum for Open Research, Sharjah (UAE) - October 2025 In Open Access Week 2015, QNL announced the launch of an open access fund aimed to enhance support for open access publishing in Qatar. This fund, which is the only national consortium-supported fund in the region, aligns with QNL's goal of providing long-term open access to all research outputs from Qatar. Since the launch of the Open Access Fund in 2016 (now rebranded as the Open Access Program), QNL has received an impressive 10,000 funding requests, highlighting the necessity for additional funding resources. The program has successfully supported 5,869 articles authored by 2,249 different authors across 44 institutions in Qatar. QNL has leveraged both reading and publishing agreements, along with partnerships with fully open-access publishers, to provide essential support for researchers in the country. However, the program has faced several challenges. This presentation will provide a brief overview of the development of the open access program over the past ten years. It will cover the transition from ad-hoc requests to the establishment of a team of administrators to manage the fund, the setup of the QNL consortium, negotiations related to the first open access agreements, and the difficulties in reaching equitable agreements with publishers, as well as establishing meaningful workflows. The most significant challenge has been securing sustainable funding. While QNL has supported almost 6,000 articles, it has also had to reject more than 4,000 requests, primarily due to limitations of funding for requests and publishing costs that fall outside of the consortium's coverage. Nearly ten years after the launch, there remains an ongoing opportunity for improved institutional support for open access among Qatari institutions. Additionally, there is a common expectation that QNL will handle all associated fees, which presents a potential area for further discussion and collaboration. In 2025, QNL conducted a survey to assess the program's effectiveness and explore areas for improvement. This presentation will show the survey findings and discuss potential improvements to the program, including changes to funding criteria and communication processes. The presentation will discuss QNL's next steps regarding the long-term sustainability of the open access fund, with plans to encourage institutions to develop more policies for open access funding and supporting the QNL consortium in financing open access initiatives. Other Information Conference information: 4th Annual Forum for Open Research, (20 - 23 October 2025, Sharjah, UAE) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://forumforopenresearch.com/2025programme/